Evaluation of acute toxicity of an aqueous extract of irradiated Labisia pumila on zebrafish embryo (Danio Rerio) - Balan, Santhra Segaran; Manokaram, Punithaamalar; Shari, Norshafarina; Mohd Uzid, Mahathir; Bahari, Hasnah; Che Ramli, Muhammad Danial; Zainal Abidin, Azrina; Rahmadi, Mahardian; Arapoc, Daryl Jesus (All India Institute of Medical Sciences, 2020)
This research aimed to compare the toxicity effect of non-irradiated and irradiated Labisia pumila at a different dosage of 3, 6, 9 and 12 kilogray (kGy). Different irradiated dosages of L.pumila were prepared using Cobalt-60 gamma irradiation and the acute toxicity were assessed through zebrafish (Danio rerio) embryo. The survival rate, hatching rate, heartbeat rate and scoliosis were observed. Data were analyzed using SPSS 25.0 windows. The lethal dose (LC50) value was calculated. The LC50 value of non- irradiated extract L. pumila is 125 μg/ml compared to irradiated extract is 62.5 μg/ml respectively. Hatchability of zebrafish of L.pumila extract reduce in the higher concentration for non-irradiated sample at 250 μg/ml and for irradiated sample at 125 μg/ml. Presence of scoliosis not observed in all concentration for irradiated and non-irradiated sample. The heartbeat of zebrafish embryo treated with irradiated L. pumila extract (0–62.5 μg/ml) was within the normal range (120–180 bpm for all doses), but at higher concentrations (125 μg/ml) the heartbeat differs from normal ranges for all the doses. From this time forward, irradiated and non-irradiated of this plant was safe to be consumed due to its pharmaceutical effect but it still exhibited mild toxicity effect on zebrafish embryo. The diverse irradiated doses show a change of toxicity level of this plant which higher doses show mild toxicity to the zebrafish embryo compared to low doses exposure.